Application of the CSM-CROPGRO-Dry bean model to optimize irrigation as a function of sowing date in common bean cultivars - Coelho, Anderson Prates [UNESP]; Faria, Rogério Teixeira de [UNESP]; Lemos, Leandro Borges [UNESP]; Cazuza Neto, Ancelmo [UNESP] (Elsevier, 2023)
Common bean is grown in tropical and subtropical regions under a wide range of pedoclimatic conditions and there is a large variation between the management practices, types of cultivars being used and the farmers' technological level. In this context, simulation models are feasible and promising alternatives for site specific management practices. This study aimed to use the CSM-CROPGRO-Dry bean model as a tool to optimize irrigation management as a function of sowing date and common bean cultivar. Two common bean cultivars IAC Imperador (determinate growth habit) and IPR Campos Gerais (indeterminate growth) were grown during two winter growing seasons in a field experiment conducted in south-eastern Brazil. The experiment included five irrigation treatments (54%, 70%, 77%, 100%, and 132% of crop evapotranspiration). After model parameterization, a long-term analysis was performed to simulate the effect of the five irrigation levels on the grain yield of common bean cultivars as a function of eight sowing dates. The results showed that irrigation may be managed under a regulated water deficit without significantly reducing common bean yields if sowing is brought forward (Mar/Apr) within the winter season. For no deficit irrigation, sowing dates in which common bean reproductive stages coincide with the period of lowest global solar radiation (GSR) should be avoided. This is because, for each unit increase in GSR after flowering, grain yields of the cultivars IAC and IPR increase by 55 and 50 kg ha−1, respectively. Therefore, the CSM-CROPGRO-Dry bean model is a powerful tool for defining more specific and sustainable irrigation management for common bean cultivars.
Keywords: Deficit irrigation; DSSAT; Growth habits; Phaseolus vulgaris L.